Moderating Role of Stock Return Volatility in Corporate Governance–Firm Value Structural Linkages : Insights from a PLS-SEM with IPMA Approach - Singh, Raj Kumar; Kumar, Naresh; Singh, Yashvardhan; Kumar, Ajay; Kumar, Sunil (Indian Journal of Finance, 2025)
Purpose : This study examined the structural linkages between corporate governance (CG) and firm value (FV) through financial performance (FP) and CEO-duality (CEOD) as mediating and stock return volatility (SRV) as moderating constructs. Design/Methodology : This research utilized secondary data derived from the annual reports of listed companies spanning the period from 2011–2012 to 2023–2024, comprising 520 company-year observations. It adopted an advanced methodological approach, a Smart partial least squares structural equation modeling (PLS-SEM) with importance-performance matrix analysis (IPMA), within a panel data framework. Findings : The findings elucidated that CG and CEOD positively and significantly impacted firm value, while FP had a positive but insignificant impact. CEOD positively and significantly mediated the CG–FV structural relationship, whereas FP mediated this relationship positively but insignificantly. The combined mediating effect of CEOD and FP was also positive but insignificant. SRV negatively and significantly moderated the CG – FV relationship. Practical/Social Implications : Effective governance boosts profitability and trustworthiness, enabling companies to attract more cost-effective capital. Improved performance yields two key benefits: high tax revenue for the government and greater CSR spending, both promoting sustainable development goals and socio-economic prosperity. Theoretical Implications : The findings demonstrated that resource dependence theory complemented agency theory while challenging the theoretical foundations of the stewardship theory. Originality/Value : This is a novel study that examined CG–FV structural linkages of the listed companies in India, utilizing the PLS-SEM methodology with IPMA.